Uptake of novel evidence-based therapies in patients with type 2 diabetes after a cardiovascular event: insights from CANHEART - Wade Thompson, PharmD, PhD; Brendan Wong, MD; Atul Sivaswamy, MSc; Laura Ferreira-Legere, MScN; Douglas S. Lee, MD, PhD; Husam Abdel-Qadir, MD, PhD; Dennis T. Ko, MD, MSc; Alanna Weisman, MD, PhD; Sheldon Tobe, MD, MSc; Cynthia A. Jackevicius, PharmD, MSc; Shaun G. Goodman, MD, MSc; Michael E. Farkouh, MD; et al. (CJC Open)
Background: A cardiovascular (CV) hospitalization is a seminal opportunity to implement guideline-directed medical therapy (GDMT). Sodium-glucose transporter 2 inhibitors (SGLT2is) and glucagon-like peptide-1 receptor agonists (GLP1RAs) can improve outcomes among those with type 2 diabetes mellitus (T2DM) and CV disease. Methods: We conducted a population-based cohort study among patients aged ≥ 66 years with T2DM in Ontario hospitalized for a CV event (myocardial infarction, heart failure, peripheral arterial disease, ischemic stroke) from June 2015 to March 2022, who were followed until March 2023. We examined use of GDMT before vs after the index event, including use of SGLT2is, GLP1RAs, statins, and others medications. Results: We identified 75,869 people aged ≥ 66 years with T2DM (median age 78 years; 43% female). The proportion receiving SGLT2is was 9% before index hospitalization and 29% during the follow-up period. GLP1RA was used for 1% before vs 9% after, compared with 65% before and 86% after for statins. Use of novel GDMT increased across the follow-up period. The incidence of SGLT2i use 1-year posthospitalization was 4% in 2016 vs 39% in 2021; for GLP1RA use, the incidence was 0% in 2016 vs 11% in 2021. Conclusions: A rise in the use of novel GDMT suggests increasing adoption of therapies to optimize secondary prevention in patients with T2DM and CV disease after index CV events. Résumé: Contexte: Une hospitalisation en raison d’une maladie cardiovasculaire (CV) est l’occasion idéale de mettre en pratique un traitement médical préconisé dans les lignes directrices. Les inhibiteurs des cotransporteurs sodium/glucose de type 2 (iSGLT2) et les agonistes du récepteur du peptide-1 apparenté au glucagon (aGLP1R) peuvent améliorer les résultats chez les patients atteints d’un diabète de type 2 (DT2) et d’une maladie CV. Méthodologie: Nous avons réalisé une étude de cohorte populationnelle, en Ontario, chez des personnes de 66 ans ou plus atteintes d’un DT2 et hospitalisées pour un événement CV (infarctus du myocarde, insuffisance cardiaque, maladie artérielle périphérique, accident vasculaire cérébral ischémique) entre juin 2015 et mars 2022, et suivies jusqu’en mars 2023. Nous avons examiné le recours aux traitements médicaux préconisés dans les lignes directrices avant et après l’événement de référence. Ces traitements comprenaient les iSGLT2, les aGLP1R, les statines et d’autres médicaments. Résultats: Nous avons recensé 75 869 personnes de 66 ans ou plus atteintes de DT2 (médiane d’âge de 78 ans; 43 % de femmes). La part d’utilisation des iSGLT2 était de 9 % avant l’hospitalisation de référence et de 29 % durant le suivi, et celle des aGLP1R était de 1 % avant et de 9 % après, en comparaison de 65 % avant et 86 % après dans le cas des statines. L’utilisation de traitements médicaux novateurs préconisés dans les lignes directrices a augmenté au cours de la période de suivi. Lorsqu’on compare l’année 2016 à l’année 2021, la fréquence d’utilisation 1 an après l’hospitalisation a été respectivement de 4 % versus 39 % pour les iSGLT2, et de 0 % versus 11 % pour les aGLP1R. Conclusions: L’utilisation accrue de traitements médicaux novateurs préconisés dans les lignes directrices indique une adoption croissante de traitements visant à optimiser la prévention secondaire chez les patients atteints d’un DT2 et d’une maladie CV après la survenue de l’événement CV de référence.